Development of a Virtual Test to Measure Mastery of Green Chemistry Material - Sanusi Noor, Dewi; Nahadi; Hernani (International Journal of Educational Research Excellence (IJERE), 2023)
This research aims to obtain a virtual test that measures proficiency in green chemistry with good instrument quality, meeting the criteria of validity, reliability, readability value, difficulty level, and good discrimination power. The virtual test in this research consists of text, images, animations, graphs, and videos. The method used is the development and validation method, which involved developing twenty items for the virtual test that have been deemed valid. First, a readability test was conducted on the items with five students, followed by a real-class trial involving 101 tenth-grade students from three high schools that already use the independent curriculum. The findings of this research show that out of the 36 developed test items, 20 items have a CVR value above 0.99, a reliability value of 0.702, categorized as high. The difficulty level test resulted in a value of 0.39, categorized as moderate, and the discrimination power test yielded a value of 0.41, categorized as good.